Terrorism Outside the Proverbial Vacuum: Implications for the Moral Context. Issue 5 (3rd May 2016) - Carson, Jennifer Varriale; Bartholomew, Brad
ABSTRACT: Prior research has found that terrorists are not susceptible to certain and severe countermeasures. One possibility is that, instead, deterrence is relative. Based on this premise and inspired by situational action theory's conceptualization of the "moral context, " this research proposes that there are circumstances that influence both moral norms and their enforcement. We hypothesize that one set of circumstances is that of high profile terrorist attacks, which in turn should decrease the hazard of future incidents. We find mixed support for our hypotheses, but maintain that it has important implications for policy.